Revisit Intention through the Development of Tourism Components and Tourist Satisfaction at Hot Spring Tourism Destinations - Rahyuniati Setiawan; Wati Susilawati (UIN Sunan Gunung Djati, 2025)
Hot spring tourism destinations in West Java face challenges in maintaining visitor satisfaction and encouraging repeat visits, particularly due to inconsistencies in tourism component development. Despite the growing interest in wellness tourism, limited studies have examined the direct and indirect relationships between tourism components, tourist satisfaction, and revisit intention in this context. This study aims to analyze the influence of tourism components on tourist satisfaction and its impact on revisit intention at hot spring tourism destinations. The research employs a descriptive and verification method with a sample of 400 respondents, selected using Random Sampling techniques. Data analysis was conducted using Structural Equation Modeling (SEM). The results indicate that Tourism Components significantly influence Tourist Satisfaction, substantially impacting Revisit Intention. However, Tourism Components do not directly influence Revisit Intention. This study underscores the importance of providing adequate facilities and better management of tourist destinations to enhance satisfaction and attract repeat visits. These findings offer valuable insights for tourism managers in their efforts to develop more competitive and sustainable hot spring tourism destinations.